Wind Tunnel Tests on Floating Offshore Wind Turbines: A Proposal for Hardware-in-the-Loop Approach to Validate Numerical Codes. Issue 6 (December 2013) - Bayati, I.; Belloli, M.; Facchinetti, A.; Giappino, S.
This paper describes the realization of a 2-DoF experimental rig, performed at Politecnico di Milano Wind Tunnel, aimed at simulating the motion of a floating wind turbine scale model, due to combined effect of hydrodynamic and aerodynamic loads. As floating offshore wind farms are becoming objects of interest among the international scientific community, experimental tests have been increasingly demanded to support dynamic and structural numerical simulations. Furthermore measurements on real prototypes are very complex and expensive and it is difficult to use these data to validate prediction models because of the uncertainties in the definition of the environmental data, such as sea state and incoming wind. The motivation of this project is to provide an experimental set-up working in a fully controlled test environment (with measurable input/output) in order to validate numerical codes. The paper describes the features of the experimental rig, the results coming from the validation tests on the rig, through a dedicated "off-line" experimental campaign and, conclusively, a proposal for a "Hardware-In-The-Loop" real time functioning mode.